PEMANFAATAN KERANG HIJAU (Mytilus viridis) DALAM PEMBUATAN HIDROLISAT PROTEIN MENGGUNAKAN ENZIM PAPAIN - TATI NURHAYATI; ELLA SALAMAH; ELIN AMALIA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2011)
Protein hydrolyzed has high protein so that can be used for food industry and also pharmacy. Existence of making product of protein hydrolyzed expected can improve fishery product become new product as food which have high protein. One of marine product which not explore yet is green cockle. It has high protein and can be made as fish protein hydrolyzed product through modification process. The aim of research are: to determine of enzyme concentration, time and hydrolysis pH for making of hydrolyzed product. Results of research indicate that best concentration of enzyme for making of hydrolyzed product is 5% (w/v), 24 hours and pH 7. Characteristic of green cockle protein hydrolyzed are: water rate is 84,44 %, dusty rate is 1,25%, protein is 11,75% and fat is 2,56%. Protein hydrolyzed product of green cockle contain of free nitrogen -amino as much as 0,88 g/100 g and also hydrolyzed degree equal to 0,47. This protein hydrolyzed product consisted of 17 kinds of amino acid.